2020
DOI: 10.3390/nano10112226
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Silicon Carbide: Emerging Direct Band Gap Semiconductor

Abstract: As a direct wide bandgap semiconducting material, two-dimensional, 2D, silicon carbide has the potential to bring revolutionary advances into optoelectronic and electronic devices. It can overcome current limitations with silicon, bulk SiC, and gapless graphene. In addition to SiC, which is the most stable form of monolayer silicon carbide, other compositions, i.e., SixCy, are also predicted to be energetically favorable. Depending on the stoichiometry and bonding, monolayer SixCy may behave as a semiconductor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 115 publications
2
47
1
Order By: Relevance
“…A detailed discussion about the structure, properties, and applications of 2D SiC has been provided in our very recent review paper [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed discussion about the structure, properties, and applications of 2D SiC has been provided in our very recent review paper [5].…”
Section: Introductionmentioning
confidence: 99%
“…The 2D form of SiC will naturally benefit from these overall SiC properties. Furthermore, as a result of reduced dimensionality and quantum confinement, 2D SiC is predicted to exhibit exotic optical and electronic properties, that are very useful for various applications [ 1 , 2 , 3 , 4 , 5 ]. Structurally, 2D SiC is predicted to have a graphene-like honeycomb structure consisting of alternating Si and C atoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bismuthene and phosphorene structures were obtained from literature references [63][64][65][66] and designed using Avogadro software [67]. Online Resource Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, works by Li and Shi et al [26,27] showed that the silicon carbon monolayer possesses high thermal stabilities such that the Si 2 C 3 and SiC 3 sheets can retain their planar geometries below 3500 K and manifest excellent properties of semiconductivity and elasticity for applications in electronics and optoelectronics. Chabi et al [28] found that 2D silicon carbide (Si x C y ) is a universal material, and exhibits the same properties as graphene, silicon or silicon carbide, depending on the composition (i.e., Si 2 C 3 , SiC 3 and SiC 4 ). For extensive exploration of novel nanostructures as potential materials for CO 2 capture, a question raised in this study is whether SiC 3 nanosheets are also a promising material for CO 2 capture, and whether its capture/separation could be efficiently tuned by the charge/electric field.…”
Section: Introductionmentioning
confidence: 99%